(untitled) (Jurnal Bahasa, 2019)
The Brunei Dusun ethnic group, also known as Sang Jati Dusun, is one of the seven ethnic groups in Brunei Darussalam. The Dusuns have their own distinctive language which is still practised by some of the members of this group today. However, many are unaware that their language has been influenced by the Brunei Malay language. The objectives of this study are to identify the influence of the Malay language on the Dusun language and the cause of the influence. There are three linguistic aspects regarding the influence of the Malay language that are discussed, which are the spelling, phonology and the language affixes of the Dusun language. The source for the main study are vocabulary items taken from Yabit’s (1994) thesis entitled The Reconstruction of Pre-Dusun and the Classification of its Descendants (2011); the book entitled Daftar Leksikal 7 Dialek Brunei Darussalam (2011); Kamus Sang Jati Dusun (2014); as well as lexical items known by the researcher. The respective vocabulary items are compared with the linguistic aspects of the Brunei Malay language. Subsequently, this paper discusses some of the possible causes that may have influenced the Dusun language. Among these are that the two languages originate from the same clusters of Austronesian, the strong cognate between the Dusun language and the Malay language, the Brunei education system, the migration of the Dusun tribes to the shoreline, and socio-economic factors. Finally, it is hoped that this study will provide additional information on the ethnic languages in Brunei and raise awareness among the Dusun community about how their language has been affected by the influence of Malay. Keywords: Brunei Dusun language, influence of Malay Language, Sang Jati Dusun, spelling, phonology, affix